Interaction in Online Tutoring Sessions: An Opportunity to Knit English Language Learning in a Blended Program - Rosa Alejandra Medina Riveros (Profile: Issues in Teachers' Professional Development)
This article reports a research study which intended to describe the interaction taking place between a tutor and her students during the online tutoring sessions (ots ) in the alex Virtual English Program at the Universidad Nacional de Colombia, in Bogotá. Students' surveys, chat transcriptions and tutor's journals were used to collect data. The results showed how language itself, the methodology of the course, reflection upon learning, and social and personal issues made up the conversational topics prevailing in these sessions. It was also found that the main interactions between the tutor and the learners consisted of double-way dynamics.